MINERAL WATER TREATMENT TECHNOLOGY USING RO MACHINES TO IMPROVE HEALTHY LIVING QUALITY & ECONOMY FOR MDT AL-KARIMAH AND THE SURROUNDING COMMUNITY - Widyanto, Muhammad Laras; Halim, Sofyan; Nugroho, Dony Ari (LPPM Univ. Ibn Khaldun Bogor, 2025)
The Community Service Program (PKM) was carried out at Madrasah Diniyah Takmiliyah (MDT) Al-Karimah, Cibunar Village, Kadudampit District, Sukabumi Regency, West Java. The background of the activity is the problem of limited access to healthy mineral water and the need to improve the economy of the MDT and the surrounding community. The solution of this program is to improve the quality of healthy living through the provision of mineral water based on Reverse Osmosis (RO) technology while empowering the economy of MDT Al-Karimah through the management of drinking water refill depots. The implementation method includes program socialization, technical and managerial training, installation of RO machines with a capacity of ±80 gallons/day, operational assistance, and sustainability evaluation. This activity is participatory, involving students, MDT administrators, and the local community, with the support of the village and sub-district governments. The results of the activity showed that the mineral water produced passed the feasibility test of the Sukabumi Regency Health Office, so it was safe for consumption. The conclusion is that this program has contributed for providing dual benefits, namely improving the quality of public health through access to hygienic drinking water and strengthening the economy of MDT-based communities.